Spatial variation in spawning timing for multi-species Acropora assemblages in the Red Sea - Osman, Eslam O.; Suggett, David J.; Attalla, Tamer M.; Casartelli, Marco; Cook, Nathan; El-Sadek, Islam; Gallab, Ahmed; Goergen, Elizabeth A.; Garcias-Bonet, Neus; Glanz, Jessica S.; Pereira, Pedro Henrique; Ramirez-Sanchez, Megan; et al. (Frontiers in Marine Science, 2024)
Sexual reproduction is a crucial process for reef building coral populations to maximize genetic diversity and recover from large scale disturbances. Mass spawning events by Acropora species represent critical opportunities for populations to persist, and a process that is increasingly exploited to actively restore degraded reefs. However, the timing and predictive capacity of coral spawning throughout the broad thermal and environmental regime of the Red Sea – a region also undergoing significant development and active reef restoration – remains patchy. We, therefore, conducted three parallel reef surveys in the central Red Sea (Al-Fahal Reef, Thuwal - Saudi Arabia) and the eastern (Shushah Island - Saudi Arabia) and western (Hurghada – Egypt) coast of the northern Red Sea. Surveys assessed the gravidity of gonads, spawning timing, alignment with the lunar cycle of 21 Acropora spp. (total n= 572 colonies) around the full moons of April and May 2023. Consistent with past observations, synchronous spawning was observed for Acropora spp. in both the central and northern Red Sea during April and May, respectively. Interestingly, corals spawned on the full moon in both Shushah and Thuwal sites. In contrast, corals in Hurghada were independent of the lunar cycle and spawned 7-9 nights before the full moon in May. By integrating our 2023 observations with the historical spawning events in Hurghada and Thuwal (2002-2022), we found that the deviation of spawning timing from the full moon day was correlated with absolute Sea Surface Temperature (SST) (earlier spawning before the full moon day, lower SST) and warming rate (earlier spawning, more rapid warming) in 6-weeks prior to spawning. As such, temperature pattern is likely one of the primary factors governing gamete release, among other factors, that likely influence spawning day within the lunar month. These correlations between SST metrics and spawning timing suggest a potential framework to predict future Acropora spp. spawning dates. Our observations demonstrate the importance of parallel efforts across borders to collect critical data needed to inform management strategies aimed at conserving and restoring coral reefs in this ecologically diverse region.